Thin film composite hollow fiber membrane for separation in biorefinery - Elfira, Anuar (2019)
Membrane technology has been well-recognized for sugar concentration and inhibitor removal during biomass processing in biorefinery. However, most of the membranes used were commercially purchased and not specifically customize for the biomass hydrolysate processing. In the current study, a series of thin film composite (TFC) hollow fiber membranes were fabricated to tailor the performance toward sugar concentration and acetic acid removal in biomass processing. Three important parameters were investigated which were type of aqueous monomer in interfacial polymerization (IP) process, air gap distance during dry-wet spinning process for fabrication of membrane substrate, and the concentration of aqueous mphenylenediamine (MPD) monomer in IP. The membranes were evaluated by permeability and solute rejection tests, scanning electron microscopy, and Fourier transform infrared spectroscopy. The best aqueous monomer obtained to prepare TFC hollow fiber membrane was MPD monomer. Hollow fiber spun at 6 cm air gap distance showed the best membrane substrate to produce TFC membrane. MPD concentration of 2.0 wt. % was selected as the best concentration to react with trimesoyl chloride organic monomer to prepare TFC hollow fiber membrane. TFC hollow fiber membrane prepared at this best condition showed the rejection value of 91.66 ± 0.09 % xylose, 67.28 ± 13.97 % glucose, and 13.08 ± 3.00 % acetic acid. This is corresponding to the ideal separation factor of 3.20 ± 1.27 for acetic acid/glucose and 10.42 ± 0.25 for acetic acid/xylose. Although, the membrane is feasible for simultaneous acetic acid removal and sugar concentration in lignocellulosic hydrolysates but its performance is still low compares to the commercial membrane. As an example, commercial RO98pHt membrane had an ideal separation factor of 223.16 for acetic acid/glucose and 348.69 for acetic acid/xylose, and RO99 membrane separation factor of 209.96 for acetic acid/glucose and 194.41 for acetic acid/xylose. Further investigation on producing membrane material with good combination of mechanical and physicochemical properties is necessary in the future study. In addition, simultaneous optimization on the membrane spinning parameters and IP process parameters can improve the performance of the TFC hollow fiber membrane. Testing the TFC membrane with real biomass hydrolysate also important to evaluate the actual TFC hollow fiber membrane performance.